The influence of underlying surface on reflectiviti of layer atmosphere; Proceedings of SPIE; Vol. 9292 : Atmospheric and Ocean Optics: Atmospheric Physics - Goryachev B. V. Boris Valentinovich (2014, 2014)
Title screen